‘Himalayasia’: Reclaiming Regional Identity in South Asia - Rusel, Md Rashidul Islam (Journal of Political Science, 2023)
South Asia is a conflict-prone region with numerous humanitarian challenges. South Asian states have long been struggling to bridge the political gaps among themselves. Regionalism has not been instrumental enough in this regard. This paper identifies a lack of regional identity for the South Asian peoples as one of the major obstacles why regionalism has never had much impact on the political map of South Asia. It is argued here that South Asia needs a major regional reorientation to reclaim its historic and cultural commonalities. And, that can be facilitated by a unique and meaningful geographical identification. In this regard, the Himalayan Mountain Range can be regarded as a geographical connector of the major South Asian States; hence, ‘Himalayasia’ could be a suitable name for their regional reorientation. The proposition is an outcome of a people-centric approach to constructing collective identity through social interaction among the peoples of South Asia based on their geographical identity and its already existing socio-cultural and civilizational legacies, which is expected to have gradual and incremental political implications in the states of this region. The research is qualitative-constructive as well as normative. It uses information, concepts and ideas from secondary sources and based on that substantiates new propositions vis-à-vis regional identity in South Asia.